Sentiment Analysis of Public Opinion on Danantara Via Social Media X - Welda Welda; Aniek Suryanti Kusuma; I Putu Robin Laksamana Putra (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
Social media has become a primary channel for the public to express opinions on various issues, including public services. One topic that has been widely discussed on platform X is Daya Anagata Nusantara (DANANTARA), a government-owned strategic investment management agency. Public sentiment toward DANANTARA is divided into three categories—positive, negative, and neutral—which may influence broader public perception. This study aims to analyze public sentiment toward DANANTARA using data obtained from platform X. The methods employed include web scraping for automated data collection and the Naïve Bayes algorithm for classifying sentiment into three labels: positive, negative, and neutral. Platform X was selected because it has over 19.5 million active users in Indonesia, making it a representative data source. From the 930 data points analyzed, it was found that public sentiment toward DANANTARA is predominantly neutral. This research is expected to provide an objective overview of public perception regarding DANANTARA.